An Analysis of Critical Thinking Skills; Global Warming Learning Materials - Hindrasti, Nur Eka Kusuma; Asikin, Nurul; Khairinnisa, Wika (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
This study aimed to analyze students' critical thinking skills levels on global warming materials. This quantitative descriptive study employed the cluster random sampling technique. The analyzed data were the students' critical thinking skills. Researchers collected the data using critical thinking skills test instruments in the form of description questions and open-ended questionnaires. Furthermore, the data were analyzed using statistical formulas in the form of percentages. Based on the data analysis results, the percentage of students' critical thinking skills score was 65% and was categorized at a moderate level. Therefore, the researchers concluded that students' critical thinking skills on global warming learning materials are moderate. Thus, there needs to be an effort to improve students' critical thinking skills.